2007
DOI: 10.1177/089686080702702s40
|View full text |Cite
|
Sign up to set email alerts
|

Association of Carnitine Deficiency in Indian Continuous Ambulatory Peritoneal Dialysis Patients with Anemia, Erythropoietin Use, Residual Renal Function, and Diabetes Mellitus

Abstract: ♦ In the present study, we aimed to determine levels of free carnitine in hemodialysis (HD) and peritoneal dialysis (PD) patients in India and to correlate carnitine deficiency with various clinical parameters. ♦ Patients on HD and PD at two tertiary care centers were selected for the study. Baseline data were obtained, and a free carnitine analysis was performed. Carnitine deficiency was defined as a free carnitine level of less than 40 μmol/L. ♦ The total number of study patients was 96 (77 on HD, 19 on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Ramalakshmi et al reported carnitine deficiency among 64.3% dialysis population in India. 68 The peritoneal dialysis patients are known to have decreased appetite and early satiety. The findings of Oreopoulos et al and Von Baeyer et al confirm that uremia, absorption of glucose and abdominal distension by the dialysate fluid are the possible causes for the loss of appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Ramalakshmi et al reported carnitine deficiency among 64.3% dialysis population in India. 68 The peritoneal dialysis patients are known to have decreased appetite and early satiety. The findings of Oreopoulos et al and Von Baeyer et al confirm that uremia, absorption of glucose and abdominal distension by the dialysate fluid are the possible causes for the loss of appetite.…”
Section: Discussionmentioning
confidence: 99%